The Development of Microsoft Access for Accounting Automation Cycle of Madrasah Aliyah Negeri (MAN) Klaten - Kabib, Nur (2012)
The objective of study are: 1) To describe the utilization of database management system, especially Microsoft Access in accounting automation Cycle of education as a part of information and communication technology. 2) To creation of database management system model by Microsoft Access as a part of information and communication technology in automation of education accounting system which can be accounted and also modified by the users' accordance with their requirements. This research is R&D research with triangulation as a method of data collecting. Furthermore, the researcher developed the data to be a developing model. The results of those developing data were tested on a research site to get a response, suggestion and appraisal from despondences. After getting response, suggestion and appraisal from despondences, then the researcher did improvement. The model which has been improved further tested again to despondences to get their appraisal if it compares with the previous result about pace of work, report accuracy, convenience of working and also appearance of model. To know the difference of average of the old system and new system are performed by t- test. The result of research shows that data base which use Microsoft access is able to fulfill the basic needs of data base that is reliability of handling the data in huge amount quickly, correct , and comfortable on research site. Besides that, data base management by Microsoft access does not hedge the flexibility of data base management as a requirement. The model which has been developed is able to increase working pace, report accuracy, convenience of work, and appearance of model. This research has several benefits and also weaknesses, however the benefits are much more than the weaknesses.